IDENTIFICATION OF TOTAL PHENOLIC AND ANTIOXIDANT ACTIVITY OF FERMENTED RICE BRAN EXTRACTED BY ELECTROLYZED WATER - Sri Mulyati; Tubagus Bahtiar Rusbana; Sulaeni Sulaeni (Food ScienTech Journal, 2020)
Fermentation of rice bran is applied to facilitating the release of and may lead to higher yields of bioactive compound in its extraction product. The use of electrolyzed water as the solvent and the influence of this water on antioxidant activity of the fermented rice bran extract compounds is unclear. The bran of white (Jalawara) and red (Marahmay) rice from Banten Province are fermented using R. oligosporus and extracted using electrolyzed water at 2.5, 6.5, 7, 9.5, and 11.5 of pH value. This research presents that Marhmay contains more active antioxidant compounds with 422.11 ppm of IC50 by DPPH evaluation method and effectively extracted by electrolyzed water at pH 2 yielded of 3% extracted phenol more than water at pH 7. Furthermore, this treatment gives insights on the potency of electrolyzed water as solvent on extraction method of biological compound.